Letter from Dr. John J. Reese to James Curtis Booth, September 17, 1859 - Reese, John J. (John James) (1859)
A follow-up to his letter of August 29 concerning negotiations to acquire a partnership share in James Curtis Booth's (1810-1888) laboratory.
Keywords: Booth, James Curtis, 1810-1888